Catholic Pentecostalism and the paradoxes of Africanization processes of localization in a Catholic Charismatic movement in Cameroon - Lado, Ludovic, 1970- (Leiden ; Boston : Brill, 2009)
The anthropological literature on religious innovation and resistance in African Christianity has tended to focus almost exclusively on what have come to be known as African Independent Churches. This book explores the dialectics between 'Pentecostalization' and 'Africanization' within contemporary African Catholicism.
List of Illustrations; Acknowledgements; General Introduction; Chapter One: From North America to Cameroon; Chapter Two: Misfortune Narratives in Ephphata; Chapter Three: A Typology of Spirit Possession; Chapter Four: Charismatic Prayer Sessions; Chapter Five: Therapeutic Strategies in Mangen; Chapter Six: Ritual Healing: Religion or Magic?; Chapter Seven: Ephphata in Paris; Chapter Eight: Paradoxes of Africanization; Chapter Nine: Anthropology and Philosophy in Africa; General Conclusion; Bibliography; Index.
Includes bibliographical references (pages 227-240) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Keywords: Hebga, Meinrad P; Ephphata (Organization); Hebga, Meinrad P; Ephphata (Organization); Hebga, Meinrad P; Ephphata (Organization); Pentecostalism -- Cameroon; Pentecostalism -- France -- Paris; Pentecostalism -- Catholic Church; RELIGION -- Christianity -- Catholic; Pentecostalism; Pentecostalism -- Catholic Church; Cameroon; France -- Paris; Charismatische Bewegung; Katholizismus; Lokalisation; Kamerun; Charismatische Bewegung; Katholizismus; Lokalisation; Kamerun; Electronic books